Cross-Cultural Psychology and Compassion - Yasuhiro Kotera; Noelia Lucía Martínez-Rives; Muhammad Aledeh; Rory Colman; Christian Veasey; Tracey Harrington; Naomi Komori; Akihiko Ozaki; Derek Griner; Yumna Ali; Elaina C. Taylor (Encyclopedia)
Cross-cultural psychology evaluates how cultural factors influence people’s behaviour and mental processes. Cross-cultural psychology aims to understand individual differences and commonalities, and to develop an appreciation, respect, and knowledge of cultures distinct from one’s own. Compassion refers to the emotional response of understanding, empathising with, and desiring to alleviate or reduce the suffering or distress of others. Compassion involves noticing the pain or difficulties another person is experiencing and being motivated to help, often characterised by acts of kindness, support, and caring. This entry paper explores the intersection of these two concepts, illustrating how insights from cross-cultural psychology can contribute to fostering compassion.